Contrafactives and Learnability - Strohmaier, David; Wimmer, Simon (Proceedings of the Amsterdam Colloquium, 2025)
Richard Holton has drawn attention to a new semantic universal, according to which (almost) no natural language has contrafactive attitude verbs. This semantic universal is part of an asymmetry between factive and contrafactive attitude verbs. Whilst factives are abundant, contrafactives are scarce. We propose that this asymmetry is partly due to a difference in learnability. The meaning of contrafactives is significantly harder to learn than that of factives. We tested our hypothesis by conducting a computational experiment using an artificial neural network. The results of this experiment support our hypothesis.